The Federal Outlines of Popular Sovereignty. Sáenz Peña’s Electoral Reform and the Citizens of the National Territories (Quinto Sol, 2021)
The citizens settled in the National Territories could not participate in national elections for almost the whole history of these spaces. A conventional approach has taken this situation as the sign of a deprivation of political citizenship that would reflect the restrictive nature of the political order imposed on the Territories. Nothing would have changed with the passing of the Sáenz Peña Law, which would have kept the settlers of the Territories excluded from citizenship.However, Sáenz Peña’s electoral reform did include the Territories and their inhabitants. Even if they remained without the possibility of voting in federal elections, it was not due to any attribution of political incapacity but to the legal status of such spaces. By studying published and unpublished documents, this paper not only questions that traditional interpretation but also aims to depict the way the principle of popular sovereignty was mediated by the federal frame of the representative regime.
Keywords: political history; citizenship; suffrage; federalism